In Vitro ACE2 and 5-LOX Enzyme Inhibition by Menthol and Three Different Mint Essential Oils - Demirci, Fatih; Karadag, Ayse Esra; Biltekin, Sevde Nur; Demirci, Betul (Sage Publications Inc, 2021)
Mentha arvensis L., M. citrata L., and M. spicata L. (family Lamiaceae) essential oils, and their characteristic constituent, menthol, were evaluated in vitro for angiotensin converting enzyme 2 (ACE2) and 5-lipoxygenase (5-LOX) enzyme inhibitory activity. The chemical compositions of M. arvensis, M. citrata, and M. spicata essential oils were analysed both by GC-FID, and GC/MS; 82.0%, 38.1%, and 0.4% menthol were identified, respectively. M. spicata essential oil contained 88.2% carvone as its major component. The enzyme inhibitory activities of the essential oils were evaluated using a fluorometric multiplate based enzyme inhibition kit; the ACE2 inhibitions produced by M. arvensis, M. citrata, and M. spicata essential oils were 33%, 22%, and 73%, while the 5-LOX inhibitions were 84%, 79%, and 70%, respectively. In addition, menthol also showed remarkable ACE2 inhibition of 99.8%, whereas the 5-LOX inhibition was 79.9%. As a result, menthol and the three different mint essential oils may have antiviral potential applications against coronaviruses due to their ACE2 enzyme inhibition and anti-inflammatory features. However, further in vivo studies are needed to confirm the safety and efficacy.
Keywords: Mentha; essential oil; ACE2; LOX; menthol